Pengaruh Legalitas Usaha, Packaging produk dan Labelisasi Halal MUI terhadap Peningkatan Volume Penjualan Produk, Usaha Mikro Kecil Menengah (UMKM) Di Kecamatan Cilacap Selatan Kabupaten Cilacap - Hakim akim (Jurakunman (Jurnal Akuntansi dan Manajemen), 2023)
The purpose of this study 1. To find out the effect of business legality on sales volume of micro, small and medium enterprise products (MSMEs) in South Cilacap District, Cilacap Regency. 2. Changing the effect of product packaging on sales volume for micro, small and medium enterprise (MSMEs) products in Cilacap Selatan District, Cilacap Regency. 3. Changing the effect of the MUI Halal Labeling on sales volume of micro, small and medium enterprise (MSMEs) products in South Cilacap District, Cilacap Regency. 4. Changing the effect of business legality, Product Packaging and MUI Halal Labeling on sales volume of micro, small and medium enterprise (MSMEs) products in South Cilacap District, Cilacap Regency.In this study using quantitative methods with the type of associative research. The sampling technique uses saturated sampling techniques. The data used is primary data. The data collection technique used a questionnaire which was distributed to 47 MSMEs in the South Cilacap District. Methods of data analysis in research, using the classical analysis assumption test, t test, f test multiple linear regression and terminationThe results of this study indicate that (1) business legality, Product Packaging and Halal Labeling have a positive and significant effect on sales volume for micro, small and medium enterprise (MSMEs) products in South Cilacap District, Cilacap Regency. (2) Product packaging has a positive and significant effect on sales volume for micro, small and medium enterprises (MSMEs) in Cilacap Selatan District, Cilacap Regency Keywords: Business Legality, Product Packaging, MUI Halal Labeling and Increasing Product Sales Volume